From Traditional Amazon Use to Food Applications: Tapirira guianensis Seed Extracts as a Triad of Antiproliferative Effect, Oxidative Defense, and Antimalarial Activity - Marcell Crispim; Thaise Caputo Silva; Amanda dos Santos Lima; Laura da Silva Cruz; Nathalia Alves Bento; Thiago Mendanha Cruz; Yasmin Stelle; Josiana Moreira Mar; Daniel de Queiroz Rocha; Jaqueline de Araújo Bezerra; Luciana Azevedo (Foods)
Tapirira guianensis is a tropical plant found in South America and is widely used by indigenous communities owing to its medicinal properties. Its seeds are rich in phenolic compounds that are known for their anti-inflammatory, antioxidant, and antimicrobial properties. Despite its traditional use, there are limited scientific data on the biological activities of its seed extracts, especially in the context of antimalarial and cytoprotective effects. In this study, we investigated the chemical composition, antioxidant potential, cytotoxic effects, and antimalarial properties of hydroethanolic, ethanolic, and aqueous seed extracts. A 1:1 (v/v) water/ethanol combination efficiently extracted bioactive compounds and delivered the highest phenolic compound content. Furthermore, the hydroethanolic extracts exhibited significant biological activities, including an ability to reduce cancer-cell viability, protect against damage caused by reactive oxygen species (ROS), and decrease chromosomal aberrations, while exhibiting high efficacy against both chloroquine-sensitive and chloroquine-resistant Plasmodium falciparum strains. Hence, the use of T. guianensis seed extract as a natural source of bioactive compounds with cytoprotective, antiproliferative, antioxidant, and antimalarial properties is innovative and highlights the need for additional in vivo studies to better elucidate its mechanisms of action and safety.